Peran Penerapan Pengendalian Internal dalam Pencegahan Kecurangan terhadap Pengelolaan Perbekalan Farmasi di Rumah Sakit Kanker “Dharmais” - Sitawati Sitawati; Hadri Mulya (UIR Press, 2018)
This study aims to determine the role of the implementation of internal control in the prevention of fraud against the management of pharmaceuticals in “Cancer hospital Dharmais” when compared with the theory and provide recommendations for the appropriate control systems applied to the management of pharmaceuticals in Cancer hospital “Dharmais”. The respondents of this study consisted of 13 civil servants involved in the management of pharmaceuticals in the Cancer hospital “Dharmais”. The method used is descriptive qualitative approach, namely by distributing questionnaires, observations, participate and in-depth interviews regarding the implementation of internal controls in the management of pharmaceuticals in Cancer Hospital “Dharmais”. There are 13 eligible questionnaires. The results of the study regarding the role of the implementation of internal control in the prevention of fraud against pharmaceutical supply management at the Cancer Hospital “Dharmais” adequate although there are still some weaknesses of internal controls which could potentially lead to fraud against the management of pharmaceutical supplies.